The Comparative Method Eilhard Wiedemann in Writing the History of Science in Islamic and Western Civilizations: A Comparative Study (Raparin Journal of Humanities (RJH), 2025)
The German physicist, historian, and orientalist Eilhard Ernst Gustav Wiedemann (1928 ce) ,by using a comparative methodology, he compared the scientific achievements of Islamic civilization and Western civilization in most of the scientific branches, particularly in fields such as(Physics and Technology). He compared the inventions and writings of Muslim scholars with those of western scholars and identified the sources of the inventions and writings of most western scholars. With scientifically proved evidence, he identified the contributions of Muslim scholars in the history of sciences. He reconstructed some of the inventions of Muslim scholars as instruments. This had a significant impact on researchers scientists and German orientalists, prompting further investigations into the history of Islamic sciences and revisiting the inventions of Muslim scholars, and he studied the history of Islamic sciences for (40) years. To study the history of Islamic sciences, he used original manuscripts of Muslim scholars as primary sources and avoided relying on Latin and Hebrew translations of the works of Muslim scholars. Between the years (1900 – 1928), with the collaboration of some German orientalists and physicists, he collected original manuscripts of Muslim scholars from most libraries in the east. He translated many of these manuscripts from Arabic into German, This research consists of four main themes: the first theme describes the scientific biography of the orientalist, the other theme compares the scientific branches, and the third theme Theoretical and practical aspects are compared. In the fourth topic, innovation between Muslim and Western scientists is compared.